2017
DOI: 10.1002/jsfa.8207
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation and fruit canopy position modify oil quality of olive trees (cv. Frantoio)

Abstract: Light and water availability are crucial not only for tree productivity, but also they clearly affect olive oil quality. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
41
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 42 publications
9
41
3
Order By: Relevance
“…More specifically, the effect of canopy position on fruit yield, size, maturity and oil content in Arbequina hedgerows was studied and higher values of these parameters were observed on the upper layers of the canopy . Canopy position can also alter the commercial and nutritional value of the olive oil, modifying fatty acid composition and total phenol content . A detailed study by Gómez‐del‐Campo et al demonstrated that fruits from higher layers of the canopy (with high light interception) yielded oil of higher stability against oxidation than fruits from lower layers of the canopy .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, the effect of canopy position on fruit yield, size, maturity and oil content in Arbequina hedgerows was studied and higher values of these parameters were observed on the upper layers of the canopy . Canopy position can also alter the commercial and nutritional value of the olive oil, modifying fatty acid composition and total phenol content . A detailed study by Gómez‐del‐Campo et al demonstrated that fruits from higher layers of the canopy (with high light interception) yielded oil of higher stability against oxidation than fruits from lower layers of the canopy .…”
Section: Introductionmentioning
confidence: 99%
“…This observation was explained by the higher composition of saturated fats and phenolic compounds in the oil extracted from fruits located in upper layers. Differences in fruits and oils from different canopy positions and orientations have shown to be related to the light intercepted on each area of the canopy . Cherbiy‐Hoffmann et al observed that shading of the fruit and leaves during maturation have consequences on oil accumulation; Trentacoste et al concluded that greater irradiance increases fruit number due to more and longer fruiting shoots that result in higher number of flower sites …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climatic conditions and different agronomic practices may influence the physiological behavior of the olive tree [58] and consequently the fruit ripening process modifying both the amount and oil quality in Olea europaea L., although the response is cultivar dependent [59][60][61].…”
Section: Olives and Olive Oil Qualitymentioning
confidence: 99%
“…In cv. Frantoio, palmitoleic and linoleic acids increased in oils obtained from fruits exposed to high solar radiation intensity, whereas oleic acid and the oleic-linoleic acid ratio decreased [61]. To overcome the negative effects of combined heat and high radiation stresses, application of kaolin in olive trees growing in rainfed conditions has been used.…”
Section: Olives and Olive Oil Qualitymentioning
confidence: 99%